The altertion kinetics curve and time-lapse imaging - Useful features in salt crystallization tests - Musacchi, J. (2014)
The decay of porous building materials due to salt crystallization is very frequent and often significant in the built heritage and, thus, a proper understanding of the underlying processes has major importance for conservation. In this light, a new method for characterization of salt decay processes was developed within the DRYMASS research project, which is based on continuously measuring by optical profilometry the micrometric changes that occur on the material surface during drying. This method produces three different types of output: the so-called "alteration curve", as well as the current gravimetric evaporation curve and time-lapse photographs of the decay. But the three features had, until now, to be recorded using different specimens. This is an important limitation because the high uncertainty of salt decay processes may give rise to different decay patterns in similar specimens. Here, we present a development of the original study, which was afterwards carried out within the same project to allow evaluating the three features in a single specimen, by using an integrated set-up. This new study was carried out with two salts often found in salt decayed constructions, Na2SO4 and NaCl, and a material frequently used in the architectural heritage, Ançã limestone. Some of the experiments were performed after application of a water repellent treatment on the stone.